2002
DOI: 10.1023/a:1014692009941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social support on children's eyewitness reports: A test of the underlying mechanism.

Abstract: Research on children's eyewitness testimony demonstrates that interviewer-provided social support given during a mock forensic interview helps children resist an interviewer's misleading suggestions about past events. We proposed and tested 1 potential mechanism underlying support effects: "Resistance Efficacy," or children's perceived self-efficacy for resisting an interviewer's suggestions. Eighty-one 6-and 7-year-old children experienced a play event, then were interviewed about the event with misleading an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
168
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(178 citation statements)
references
References 59 publications
9
168
1
Order By: Relevance
“…A considerable amount of research has examined the effects of rapport-building on child witness recall within an investigative interview (e.g., Almerigogna, Ost, Bull & Akehurst, 2007;Carter, Bottoms & Levine, 1996;Davis & Bottoms, 2002;Hershkowitz, 2011). This research generally supports the notion that a comfortable environment increases child witness recall accuracy and reduces susceptibility to misinformation.…”
Section: Effects Of Rapport-building On Eyewitness Recallmentioning
confidence: 55%
See 2 more Smart Citations
“…A considerable amount of research has examined the effects of rapport-building on child witness recall within an investigative interview (e.g., Almerigogna, Ost, Bull & Akehurst, 2007;Carter, Bottoms & Levine, 1996;Davis & Bottoms, 2002;Hershkowitz, 2011). This research generally supports the notion that a comfortable environment increases child witness recall accuracy and reduces susceptibility to misinformation.…”
Section: Effects Of Rapport-building On Eyewitness Recallmentioning
confidence: 55%
“…Similarly, other researchers have noted that the decrease in suggestibility may be the result of a fostered sense of empowerment, improving the child's resistance to suggestibility (Carter et al, 1996;Davis & Bottoms, 2002). …”
Section: Rapport-building and Suggestibilitymentioning
confidence: 91%
See 1 more Smart Citation
“…Also, with the exception of Burgwyn-Bailes et al, 2001), 9 this effect was obtained for older children and not for preschoolers. For example, Davis and Bottoms (2002) found that children who felt confident about telling an adult he or she was wrong succumbed to few misleading questions, if the children were older than 6.5 years and if they were interviewed by a supportive interviewer. In other words, the supportive interviewer increased older children's feelings of self-efficacy which in turn lowered (Gudjonsson, 1989); RCMAS ¼ Revised Children's Manifest Anxiety Scale (Reynolds & Richmond, 1978); EAS ¼ Emotionality, Activity, and Sociability Temperament Questionnaire (Buss & Plomin, 1984); CTS ¼ Carey Temperament Scales Behavioural Style Questionnaire (McDevitt & Carey, 1996); CBQ ¼ Children's Behaviour Questionnaire (Rothbart et al, 1994); TABC ¼ Temperament Assessment Battery for Children (Martin, 1988); CSDS ¼ Children's Social Desirability Scale (Crandall, Crandall, & Katkovsky, 1965); CSDC ¼ Comprehensive Social Desirability Scale for Children (Walsh, Tomlinson-Keasey, & Klieger, 1974); DICE ¼ DissociationImagination-Compliance Event Checklist (Shapiro & Purdy, 2004); bizarre questions based on Hughes and Grieve (1980) and Pratt 1990); CTI ¼ Child Temperament Inventory (Buss & Plomin, 1984).…”
Section: Social Engagementmentioning
confidence: 99%
“…In addition, it is recommendable to reduce stress in the child witness. The criminal investigation is likely to induce feelings of anxiety and inadequacy (Davis & Bottoms, 2002;Saywitz & Camparo, 1998), which may hamper the child's participation. Stress reduction can be achieved by a short relaxation procedure (e.g.…”
mentioning
confidence: 99%